The Relationship between U.S. Quantitative Easing Policy, Interest Rate Spread, and Control of Corruption on Short-Term Debt in Developing ASIAN Countries - Aini, Halia Butra; Igamo, Alghifari Mahdi; Liliana, Liliana; Riandi, Muhammad Vicky (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2025)
This study examines the impact of U.S. Quantitative Easing (QE), Interest Rate Spread, and Control of Corruption on Short-Term Debt in developing Asian countries. Using panel data from Indonesia, Thailand, the Philippines, Vietnam, and China from 2000 to 2022, the analysis employs a Random Effect Model (REM) approach. The findings reveal that U.S. QE has a positive and significant impact, indicating that increased global liquidity encourages short-term borrowing in these economies. Conversely, Interest Rate Spread negatively affects short-term debt, suggesting that higher spreads reduce reliance on external short-term financing. Additionally, stronger Control of Corruption is associated with lower short-term debt levels, highlighting the role of governance in reducing financial vulnerabilities. These results underscore the importance of maintaining prudent monetary and fiscal policies to manage external debt risks. Policymakers should strengthen governance frameworks, ensure balanced interest rate policies, and develop strategies to mitigate risks from external financial shocks. By improving institutional quality and promoting long-term financing stability, developing Asian economies can enhance financial resilience and reduce excessive reliance on volatile short-term debt.